The coiled-coil of the human Rad50 DNA repair protein contains specific segments of increased flexibility - van Noort, John (National Academy of Sciences, 2003)
Protein structural features are usually determined by defining regularities in a large population of homogeneous molecules. However, irregular features such as structural variation and flexibility are likely to be missed, despite their vital role for their biological function. In this paper, we report the observation of striking irregularities in the flexibility of the coiled-coil region of the human Rad50 DNA repair protein. Existing methods to quantitatively analyze flexibility are applicable to homogeneous polymers only. Because protein coiled-coils cannot be assumed to be homogeneous, we develop a method to quantify the local flexibility from high-resolution atomic force microscopy images. Indeed, in Rad50 coiled-coils, two positions of increased flexibility are observed. We discuss how this dynamic structural feature is integral to Rad50 function.